BRAF Mutants Evade ERK-Dependent Feedback by Different Mechanisms that Determine Their Sensitivity to Pharmacologic Inhibition - Yao, Zhan; Torres, Neilawattie M; Tao, Anthony; Gao, Yijun; Luo, Lusong; Li, Qi; de Stanchina, Elisa; Abdel-Wahab, Omar; Solit, David B; Poulikakos, Poulikos I; Rosen, Neal (Cancer cell, 2015)
ERK signaling requires RAS-induced RAF dimerization and is limited by feedback. Activated BRAF mutants evade feedback inhibition of RAS by either of two mechanisms. BRAF V600 mutants are activated monomers when RAS activity is low; all other activating BRAF mutants function as constitutive RAS-independent dimers. RAF inhibitors effectively inhibit mutant monomers, but not dimers; their binding to one site in the dimer significantly reduces their affinity for the second. Tumors with non-V600E BRAF mutants are insensitive to these drugs, and increased expression of BRAF V600E dimers causes acquired resistance. A compound that equally inhibits both sites of mutant RAF dimers inhibits tumors driven by either class of mutants or those BRAF V600E tumors with dimer-dependent acquired resistance to monomer-specific inhibitors.